Studi Perubahan Garis Pantai dengan Metode DSAS (Digital Shoreline Analysis System) Sebagai Upaya Identifikasi Erosi di Pantai Utara Pulau Tarakan - Edy Utomo; Muhammad Djaya Bakri (Borneo Engineering : Jurnal Teknik Sipil, 2023)
The beach is an area on the edge of the sea which experiences the influence of sea water fluctuations. Between the coast and the mainland separated by an imaginary line called the coastline. One of the problems on the coast is the decline of the coastline (Abrasion) and the progress of the costline (Accretion). Beaches that must be protected from the phenomenon of Abrasion and Accretion needs to be identified first to find out how far the changes have occurred in the coastline. The beach which is the object of this study is the beach on the north side of Tarakan Island. Identification was carried out by applying the DSAS Method (Digital Shoreline Analysis System) with change analysis using the LRR Method (Linear Regression Rate) and RMSE Method (Root Mean Square Error) while the mold delineation coastline based on Landsat satellite imagery in 1988, 1990, 2010, 2016, 2022, and 2023. The results of studies conducted in this study indicate that there has been a decline in the coastline with an average rate of change of 2,16 Meter/year and is predicted to increase backward an average of 0,74 Meter/year in 2033 for sandy beach areas. While in other areas there is progress of the coastline which is estimated to have a rate increase of an average of 2,40 Meter/year for Mangrove vegetation areas and an average of 0,19 Meter/year for community residential areas in 2033.